Influence of bleaching regimen and time elapsed on microtensile bond strength of resin composite to enamel - Fulya Toksoy Topcu; Ugur Erdemir; Emre Ozel; Murat Tiryaki; Elif Aybala Oktay; Esra Yildiz (Wolters Kluwer Medknow Publications, 2017)
Objectives: The aim of this study was to evaluate the effects of time elapsed since bleaching and different bleaching regimens on the microtensile bond strength of resin composite to enamel. Methodology: Forty flattened buccal enamel surfaces were divided into four groups: An unbleached (control) group and three bleaching groups. Control group specimens were not subjected to a bleaching regimen (Group 1), while those in the bleaching groups were bleached as follows: opalescence 10% (Group 2), whiteness perfect 16% (Group 3), and whiteness hydrogen peroxide 35% (Group 4). Thereafter, the bleached specimens were divided into three subgroups (n = 4 teeth each) for restoration according to predetermined posttreatment time intervals (immediately, 1 week, and 2 weeks). Bonded specimens were then sectioned and subjected to μTBS testing. The data were analyzed using Kruskal-Wallis and Mann-Whitney U-tests at α = 0.05. Results: There was a significant difference in the μTBS of the resin composite to enamel in groups that were bonded immediately after bleaching and in the control group (P < 0.05). Compared to the control group, the μTBS in Groups 2, 3, and 4 decreased significantly 1-week postbleaching (P < 0.05). No significant difference in μTBS was observed between the bleached and unbleached groups 2 weeks after treatment (P > 0.05). Conclusions: Adhesive restorative procedures could not be performed immediately or after 1 week irrespective of the type or concentration of bleaching system used. Composite restorations on bleached enamel surfaces should be performed after an interval of at least 2 weeks.